Italian Music at the Danish Court during the Reign of Christian IV: Presenting a picture of cultural transformation - Moe, Bjarke (Danish Yearbook of Musicology, 2011)
During the era of the art-loving King Christian IV, the Danish court was influenced by Italian culture. So far, this fascination has been described as being based on an ‘ad fontes’ movement and a search for what was ‘original’. The use of Italian culture in the early modern days, however, was not universal throughout Europe, but was adapted to local traditions. The article argues that the uses of Italian music at the Danish court were determined by local traditions. By showing examples of how madrigals were performed at court, it is revealed that Italian music was transformed in order to fit local circumstances. Furthermore, based on what we know about Italian musicians employed at court, it is argued that the musical activities were shaped on the balance between local and Italian music traditions.